Orai3 is an estrogen receptor α‐regulated Ca2+ channel that promotes tumorigenesis. Issue 1 (19th September 2012) - Motiani, Rajender K.; Zhang, Xuexin; Harmon, Kelly E.; Keller, Rebecca S.; Matrougui, Khalid; Bennett, James A.; Trebak, Mohamed
Abstract : Store‐operated Ca 2+ entry (SOCE) encoded by Orai1 proteins is a ubiquitous Ca 2+ ‐selective conductance involved in cellular proliferation and migration. We recently described up‐regulation of Orai3 channels that selectively mediate SOCE in estrogen receptor α‐expressing (ERα + ) breast cancer cells. However, the connection between ERα and Orai3 and the role of Orai3 in tumorigenesis remain unknown. Here, we show that ERα knockdown decreases Orai3 mRNA (by ~63%) and protein (by ~44%) with no effect on Orai1. ERα knockdown decreases Orai3‐mediated SOCE (by ~43%) and the corresponding Ca 2+ release‐activated Ca 2+ (CRAC) current (by ~42%) in ERα + MCF7 cells. The abrogation of SOCE in MCF7 cells on ERα knockdown can be rescued by ectopic expression of Orai3. ERα activation increased Orai3 expression and SOCE in MCF7 cells. Epidermal growth factor (EGF) and thrombin stimulate Ca 2+ influx into MCF7 cells through Orai3. Orai3 knockdown inhibited SOCE‐dependent phosphorylation of extracellular signal‐regulated kinase (ERK1/2; by ~44%) and focal adhesion kinase (FAK; by ~46%) as well as transcriptional activity of nuclear factor for activated T cells (NFAT; by ~49%). Significantly, Orai3 knockdown selectively decreased anchorage‐independent growth (by ~58%) and Matrigel invasion (by ~44%) of ERα + MCF7 cells with no effect on ERα – MDA‐MB231 cells. Moreover, Orai3 knockdown inhibited ERα + cell tumorigenesis in immunodeficient mice (~66% reduction in tumor volume). These data establish Orai3 as an ERα‐regulated channel and a potential selective therapeutic target for ERα + breast cancers.—Motiani, R. K., Zhang, X., Harmon, K. E., Keller, R. S., Matrougui, K., Bennett, J. A., Trebak, M. Orai3 is an estrogen receptor α‐regulated Ca 2+ channel that promotes tumorigenesis. FASEB J. 27, 63–75 (2013). www.fasebj.org